THE COMMUNITY BASED MOSQUE MANAGEMENT INDEX IN TRENGGALEK REGENCY, EAST JAVA - Rosidin Rosidin (Jurnal Dialog, 2018)
English The mosque is a center for community development that needs to be well managed. This paper sheds light on the index of and the priority aspects of mosque management in Trenggalek Regency. The research takes benefit of quantitative analysis. Validity and reliability test determined 26 items in the questionnaire. The study involved 100 respondents as sample obtained by random sampling method. The management principles that are analyzed consist of planning, organizing, actuating and controlling. The data were processed using excel program. The study showed that: 1) The index of mosque management in Trenggalek Regency was 70,25 at good category; 2) The Overall management principles implemented were at the category of good. Out of the four principles, the actuating principle was at the lowest category of 63.50 although it was still considered good. Therefore, the study suggested the priority of improvement without neglecting the other aspects of management. Indonesia Masjid merupakan sentra pembinaan masyarakat pemeluk Islam sehingga harus dikelola dengan baik. Tulisan ini menggambarkan indeks pengelolaan masjid dan menganalisis aspek prioritas pengelolaan masjid di Kabupaten Trenggalek. Pendekatan penelitian yang digunakan adalah kuantitatif. Pengujian validitas dan reliabilitas menghasilkan 26 item yang valid dan reliable untuk digunakan sebagai instrumen penelitian. Jumlah sampel yang terlibat dalam penelitian adalah 100 yang didapatkan dengan metode random sampling. Aspek pengelolaan masjid yang dianalisis meliputi perencanaan, pengorganisasian, pelaksanaan dan pengawasaan. Data yang diperoleh diolah menggunakan excel. Hasil penelitian menyatakan: 1) Indeks pengelolaan masjid di Kabupaten Trenggalek sebesar 70,25 masuk kategori baik; 2) Semua aspek pengelolaan yang diteliti berkategori baik. Dari keempat aspek, pelaksanaan mempunyai point terendah. 3) Aspek pengelolaan masjid terendah adalah pelaksanaan sebesar 63,50 masih masuk kategori baik, sehingga prioritas perbaikan, tanpa mengabaikan aspek lain.